TFA-promoted sulfonation/cascade cyclization of 2-propynolphenols with sodium sulfinates to 4-sulfonyl 2H-chromenes under metal-free conditions. Issue 17 (26th July 2019) - Yang, Tao; Kou, Peihao; Jin, Fengyan; Song, Xian-Rong; Bai, Jiang; Ding, Haixin; Xiao, Qiang; Liang, Yong-Min
Abstract : A novel, efficient and metal-free cascade sulfonylation/cyclization of 2-propynolphenols with commercially available sodium sulfinates was developed for the synthesis of 4-sulfonyl 2 H -chromenes under mild conditions. Abstract : A novel, efficient and metal-free cascade sulfonylation/cyclization of 2-propynolphenols with commercially available sodium sulfinates was developed for the synthesis of 4-sulfonyl 2 H -chromenes under mild conditions. The reaction occurred by the sodium sulfinates' nucleophilic addition of the allylene carbocation intermediate followed by a 6-endo-trig pathway. Additionally, this approach avoids the use of an oxidant or a photo-radical inducer and the reaction can tolerate a wide variety of functional groups in good yields.